Amalgamation evaluation model design based on modification weighted product-Provus-Alkin-Rwa Bhineda - Dewa Gede Hendra Divayana; P. Wayan Arta Suyasa; I Putu Wisna Ariawan (Institute of Advanced Engineering and Science, 2024)
The new normal era allowed learning at IT vocational schools to be carried out directly (synchronously) through online meeting platforms and indirectly (asynchronously) through email, WhatsApp groups, and learning management system (LMS). However, the reality showed that not all synchronous and asynchronous learning implementations were effective. Based on these problems, it was necessary to evaluate and used an appropriate evaluation model. A breakthrough was used, namely the Amalgamation evaluation model based on the modification of the weighted product with the Provus and Alkin models in view of the Rwa Bhineda concept. The purpose of this research was to show the Amalgamation evaluation model design based on weighted product modification with the Provus and Alkin models in view of the Rwa Bhineda concept as the basis for determining the dominant indicators that need to be maintained for the synchronous-asynchronous learning effectiveness. This research used a development approach that focused on the design, initial trial, and initial trial revision. The analysis of this study results used a quantitative descriptive technique, namely the percentage descriptive calculation. This research results showed the evaluation model design was good categorized as evidenced by the average percentage of effectiveness was 88.67%. The emerging significance and value of this research results was the existence of innovation in the educational evaluation field, which makes it easier for evaluators to determine the dominant indicators that need to be maintained in supporting the effectiveness of synchronous-asynchronous learning implementation in IT vocational schools generally, and specifically in IT vocational schools in Bali.